1962
DOI: 10.1128/jb.83.5.1017-1024.1962
|View full text |Cite|
|
Sign up to set email alerts
|

In Vitro Effects of C-Reactive Protein on Phagocytosis

Abstract: Carbonyl iron spherules, Diplococcus pneumoniae types Ils and XXVIIs, and Serratia marcescens were phagocytosed more rapidly and in greater numbers by leukocytes of normal human blood after incubation with C-reactive protein. With the exception of carbonyl iron spherules, addition of C-reactive protein to whole blood containing substrate had little effect on the extent of phagocytosis. Normal and acute-phase seromucoid Escherichia coli lipopolysaccharide and crude endogenous pyrogen were without a stimulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1977
1977
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 15 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…This interaction of CRP to these compounds, especially C-polysaccharide, lecithin, and tissue polycations, has been shown to activate the human classic complement pathway and thus the release of physiologically active fragments, such as anaphylatoxin and chemotactic factors, of the classic C pathway (1,2,29,30,61,84,128-135). Similarly, the ability of CRP to bind various bacterial and tissue membranes probably contributes to the enhanced phagocytic activity of peripheral granulocytes in vitro, as shown by several investigators (39,53,136,137), although others (138) have shown no phagocytic enhancement using different test procedures. Binding of CRP to DNA with subsequent solubilization via complement activation has been suggested as one of the major functions of CRP (1 39).…”
Section: Characterization Of Crp: Physical Chemical and Biologicalmentioning
confidence: 84%
“…This interaction of CRP to these compounds, especially C-polysaccharide, lecithin, and tissue polycations, has been shown to activate the human classic complement pathway and thus the release of physiologically active fragments, such as anaphylatoxin and chemotactic factors, of the classic C pathway (1,2,29,30,61,84,128-135). Similarly, the ability of CRP to bind various bacterial and tissue membranes probably contributes to the enhanced phagocytic activity of peripheral granulocytes in vitro, as shown by several investigators (39,53,136,137), although others (138) have shown no phagocytic enhancement using different test procedures. Binding of CRP to DNA with subsequent solubilization via complement activation has been suggested as one of the major functions of CRP (1 39).…”
Section: Characterization Of Crp: Physical Chemical and Biologicalmentioning
confidence: 84%
“…Several earlier studies of CRP as a bacterial opsonin have produced conflicting results. Hokama et al (15) reported increased phagocytosis by PMN in whole blood of S. pneumoniae serotypes 2 and 27 and of Serratia marcescens pretreated with CRP. Williams and Quie (30) were unable to show any effect of CRP in the presence or absence of serum on killing of S. pneumoniae or other bacteria by PMN.…”
Section: Discussionmentioning
confidence: 99%
“…Injection of mice with CRP has been found to have a protective effect against infection with S. pneumoniae serotype 3 or 4 (20). Earlier reports of CRP opsonization of bacteria in vitro (15,17,30) have been conflicting.…”
mentioning
confidence: 99%
“…The precise role of increased synthesis, transport, and secretion of acute-phase reactants during infection remains to be determined, but may be purposeful (45). For example, it has been shown that C-reactive protein can stimulate the phagocytosis by leukocytes of living pathogenic and nonpathogenic bacteria (24,29,30). Potentially harmful proteinases released at sites of tissue damage can be complexed with serum alor a2-macroglobulin and rapidly eliminated from the circulation by fixed tissue phagocytes such as rabbit alveolar or peritoneal macrophages (12,16).…”
Section: Discussionmentioning
confidence: 99%